Endogenous Clotting Factor Activity and Long-term Outcome in Patients with Moderate Haemophilia - Fischer, K.; van der Bom, J. G.; Mauser-Bunschoten, E. P.; Roosendaal, G.; Beek, F. J. A.; de Kleijn, P.; Grobbee, D. E.; van den Berg, H. M. (Thrombosis and Haemostasis, 2000)
In order to address the question of the optimum target level for prophylactic treatment of severe haemophilia patients, the association between endogenous clotting factor activity and outcome was studied in a cohort of 46 patients with moderate haemophilia. Data on treatment and outcome were collected annually.Median follow-up was 8.0 years (range 1-26). Median joint bleed frequency was 1 per year and median radiological score according to Pettersson was 1 point (max. 78) at the age of 25 years. One percent increase in clotting factor level was associated with a 4 months later onset of joint bleeds (95% Confidence Interval (CI): 2-6 months) and a 16% lower Pettersson score (95% CI: 3-27%). No statistically significant effect of clotting factor activity on joint bleed frequency could be demonstrated.These findings confirm that patients with moderate haemophilia experience only mild arthropathy, and provide evidence for a protective effect of higher clotting factor levels on joint damage.
Keywords: Moderate haemophilia; Pettersson score; haemarthrosis; arthropathy; prophylactic treatment